Students’ Attitude Toward Open AI ChatGPT in Writing Academic Articles - Hidayat, Agus; Sujarwati, Iis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The study analyzed the perspectives of English Education Department students on Chat-GPT in academic writing. The results showed that students have positive attitudes towards AI, stating it enhances grammar, sentence structure, rephrasing, and idea expansion. However, they also believe AI can hinder innovation, encourage plagiarism, and foster reliance, which can hinder the overall academic writing process. The study used a qualitative methodology and questionnaires to gather data.